Bioinformatic and experimental identification and characterization of Clostridioides difficile lipoproteins as potential vaccine candidates - Chakraborty, Soumyadeep; Heuler, Joshua; Wang, Shaohui; Qin, Junling; Roy, Adrit; Agbendeh, Lubem Nathanel; Tomatsidou, Anastasia; Kim, Hyeun Bum; Sun, Xingmin (Frontiers in Immunology, 2025)
IntroductionTreatment options for C. difficile infection are limited, with very high rates of recurrence. Active vaccination provides an attractive opportunity to prevent C. difficile infection (CDI) and recurrence. In a search for potential surface-exposed antigens involved in C. difficile colonization, two putative lipoproteins, designated LP1 and LP2, were identified from C. difficile R20291.MethodsLipoprotein sequences were aligned, analyzed, and evaluated for their immune properties. The antigenic characteristics of both LP1 and LP2 were assessed in silico and in a mouse model of immunization and CDI.ResultsMultiple sequence alignments showed that the lipoprotein sequences were highly conserved among various ribotypes. In silico analysis predicted that LP1 and LP2 possess cytotoxic T-lymphocyte, helper T-lymphocyte, and B-cell epitopes with antigenic and immunogenic properties. Immune simulation provided insights into the ability of LP1 and LP2 to stimulate humoral and cellular immune responses. These properties were further examined in a mouse model of immunization and CDI. After three immunizations at 12-day intervals, significant amounts of IgG and IgA antibodies were detected in sera and feces. LP1 and LP2 immunizations provided mice with intermediate and higher levels of protection, respectively, against R20291 infection, and significantly reduced C. difficile spore and toxin levels in feces. Furthermore, anti-LP1 and anti-LP2 sera significantly inhibited adhesion of R20291 vegetative cells to HCT-8 gut epithelial cells.DiscussionThese results indicate that both lipoproteins play a significant role in C. difficile adhesion and that LP1 and LP2 are promising immunogens for preventing C. difficile colonization.